MALTODEXTRIN IN HIGH STRENGTH EXERCISES AND THE IMPLICATING FACTORS FOR GLYCEMIC INDEX VALUES (CIPEEX, 2022)
MALTODEXTRIN IS A CARBOHYDRATE KNOWN FOR ITS VARIOUS FUNCTIONS, SUCH AS ENERGY SUPPLY OVER TIME, DELAYED FEELING OF FATIGUE DURING PHYSICAL ACTIVITIES AND CONTROL OF CHANGES IN GLYCEMIC BEHAVIOR. THE AIM OF THIS RESEARCH WAS TO EVALUATE THE USE OF MALTODEXTRIN AND ITS INFLUENCE ON INTERMITTENT EXERCISES AND GLYCEMIC RESPONSE DURING STRENGTH TRAINING, BASED ON BIBLIOGRAPHIC DATA.  THE BIBLIOGRAPHIC SURVEY WAS CONDUCTED BY THE VIRTUAL HEALTH LIBRARY IN THE ELECTRONIC DATABASES SCIELO - SCIENTIFIC ELETRNICA LIBRAY ONLINE, MEDLINE - LITERATURA INTERNACIONAL EM CINCIAS DA SAÚDE, GOOGLE ACADŠMICO - GOOGLE SCHOLAR. HEALTH TERMINOLOGY WAS USED IN THE DESCRIPTORS MALTODEXTRIN; MALTODEXTRIN AND RESISTANCE EXERCISES; MALTODEXTRIN SUPPLEMENTATION; MALTODEXTRIN AND STRESS EXERCISE, AND ONLY ORIGINAL ARTICLES PUBLISHED BETWEEN 2012 AND 2022 WERE SELECTED. THE RESULTS FOUND SUGGEST AN INCREASE IN PRE-EXERCISE GLYCEMIA AFTER INGESTION OF A CARBOHYDRATE DRINK, NOT ALTERING THE CONCENTRATION OF MUSCLE GLYCOGEN, THUS NOT REFLECTING FATIGUE DELAY DURING STRENGTH TRAINING. ALTHOUGH BLOOD GLUCOSE INCREASED AFTER CARBOHYDRATE INGESTION, IT RETURNED TO BORDERLINE VALUES, REMAINING SO UNTIL THE END OF THE EXERCISE SESSION. FOR STRENGTH TRAINING, WHAT CAN BE CONCLUDED IS THE NEED FOR MORE RELEVANT STUDIES, AS WELL AS THE OBSERVATION OF IMPORTANT VARIABLES IN THIS TYPE OF STRENGTH EXERCISE, SUCH AS HEART RATE AND LACTATE CONCENTRATION
Keywords: maltodextrin; maltodextrin and resistance exercises; maltodextrin supplementation; maltodextrin and strength exercise